Inovasi Kemasan Kopi Robusta Kekinian Desa Sukamaju Berbasis Kearifan Lokal - Yuliani, Dini; Nursetiawan, Irfan; Taufiq, Otong Husni (Universitas Muhammadiyah Sidenreng Rappang, 2021)
Poverty is still the main topic as a problem that must be resolved and an indicator of the existence of a pre-prosperous society, and this cannot be separated from the factor of economic inequality and the inability of the community to meet their basic needs. Poverty can also mean a lack of social needs and economic inability. As for the objectives of this activity, namely: (1) Socializing contemporary coffee packaging as an adaptive and novelty form of packaging in the modern era; (2) Providing training on the creativity of coffee farmers in coffee making and providing great opportunities in promoting superior products of coffee producers; and (3) Providing business assistance for coffee producers. The method used in this service activity, namely: Focus Group Discussion (FGD) to determine the potential of the coffee-producing community and using the Waterfall method. The results of these activities, namely (1) Coffee packaging innovations that have been carried out have received positive responses from partners and are useful for increasing the number of sales of coffee commodity products; (2) Coffee packaging innovations consist of information on Brand Coffee, Single Origin and Espresso Blend, region, varietal, roast level, cupping notes, height, weight of coffee, roast date, beans, and level of fineness; (3) Community service is carried out through socialization of coffee packaging innovations, packaging design training, and business assistance; and (4) Business assistance with partners includes training in partner organization management, assistance in program development, as well as monitoring and evaluation of activities.